The influence of staff training and education on prosthetic and orthotic service quality: A scoping review. (June 2018) - Forghany, Saeed; Sadeghi-Demneh, Ebrahim; Trinler, Ursula; Onmanee, Pornsuree; Dillon, Michael P; Baker, Richard
Background: Education and training in prosthetics and orthotics typically comply with International Society for Prosthetics and Orthotics standards based on three categories of prosthetic and orthotic professionals. Objective: This scoping study sought to describe the evidence base available to answer the question, How are prosthetic and orthotic services influenced by the training of staff providing them? Study design: Scoping review. Methods: A structured search of the peer-reviewed literature catalogued in major electronic databases yielded 3039 papers. Following review of title and abstract, 93 articles were considered relevant. Full-text review reduced this number to 25. Results: Only two articles were identified as providing direct evidence of the effects of training and education on service provision. While both suggested that there was an impact, it is difficult to see how the more specific conclusions of either could be generalised. The other 23 articles provide a useful background to a range of issues including the specification of competencies that training programmes should deliver (3 articles), descriptions of a range of training programmes and the effects of training and education on student knowledge and skills. Conclusion: Although it is considered axiomatic, the service quality is dependent on practitioner education and training. There is insufficient evidence to establish whether levels of training and education in prosthetics and orthotics have an effect on the quality of prosthetic and orthotic services. Clinical relevance: There is very little evidence about the effects of training and education of prosthetists and orthotists on service quality. While this is a somewhat negative finding, we feel that it is important to bring this to the attention of the prosthetics and orthotics community.